Electric Vehicle Business Models Global Perspectives - Beeton, David; Meyer, Gereon (Lecture Notes in Mobility, 2015)
This contributed volume collects insights from industry professionals, policy makers and researchers on new and profitable business models in the field of electric vehicles (EV) for the mass market. This book includes approaches that address the optimization of total cost of ownership. Moreover, it presents alternative models of ownership, financing and leasing. The editors present state-of-the-art insights from international experts, including real-world case studies. The volume has been edited in the framework of the International Energy Agency's Implementing Agreement for Cooperation on Hybrid and Electric Vehicles (IA-HEV). The target audience primarily comprises practitioners and decision makers but the book may also be beneficial for research experts and graduate students. .